The Predictors of Foreign Tourists' demand of Mongolia: the Application of Gravity Model - Enkhbat, Amarjargal; Tegshjargal, Sodnomdavaa (Mongolian Journal of Economic Review, 2025)
The tourism sector makes a significant contribution to the economy, society, and the environment. In recent years, the number of foreign tourists visiting in Mongolia has dramatically increased due to Mongolian government has successfully implemented the comprehensive measures to develop the tourism sector and attract foreign tourists more to Mongolia. However, there is a need to enhance the competitiveness of the tourism sector of Mongolia as well as improve the certain challenges including geographical, external and internal issues in the tourism sector of Mongolia. As a result of the successful implementation of the “Go Mongolia” held by the Mongolian government, the demand for foreign tourists to travel to Mongolia has been growing up gradually after Covid. Therefore, the aim of present study is to analysis the determinants of foreign tourism demand to Mongolia by utilizing an gravity model with panel data, which included the leading 28 tourist countries visiting in Mongolia for the 2000–-2023 period. According to the results of the regression analysis, the variables including GDP per capita of the visiting country, border dummy variable, and expenditure per foreign tourist were statistically significant positive. The results of the present study indicate that these variables are positively related to the demand for foreign tourists to Mongolia, while a distance between countries and the provision of sanitation facilities in Mongolia were negatively related. Гадаадын жуулчдын Монгол Улсад аялах эрэлтэд нөлөөлөх хүчин зүйлсийн шинжилгээ: Таталцлын загварын аргыг ашиглах нь Хураангуй: Аялал жуулчлалын салбар нь эдийн засаг, нийгэм, байгаль орчинд тодорхой хувь нэмэр оруулдаг салбар билээ. Сүүлийн жилүүдэд гадаадын орнуудаас Монголд аялах жуулчдын тоо нэмэгдэж, мөн Засгийн газраас аялал жуулчлалын салбарыг хөгжүүлэх цогц арга хэмжээнүүдийг амжилттай хэрэгжүүлж байгаа хэдий ч газар зүй, гадаад болон дотоод нөхцөл байдалтай холбоотой олон үзүүлэлтүүдийг сайжруулах, аялал жуулчлалын салбарын өрсөлдөх чадварыг дээшлүүлэх шаардлагатай байна. Монгол Улсын Засгийн газраас “Go Mongolia” арга хэмжээг амжилттай хэрэгжүүлсний үр дүнд гадаадын жуулчдын Монголд аялах эрэлт нэмэгдэж байна. Иймд Монголд аялах гадаадын жуулчдын эрэлтэд ямар хүчин зүйлс нөлөөлж байна уу гэсэн асуултад хариулт өгөх зорилгоор 2000-2023 оны хугацааны тэргүүлэх жуулчлагч 28 орны панел өгөгдөлтэй Таталцлын загварыг ашиглан регресийн шинжилгээ хийсэн. Регрессийн шинжилгээний үр дүнгээр гадаадын жуулчдын Монголд аялах эрэлтэд аялагч орны нэг хүнд ногдох ДНБ, хиллэдэг эсэх байдал, гадаадын нэг жуулчнаас гарах зардал зэрэг үзүүлэлтүүд нь эерэг, харин улс хоорондын зай болон Монголын ариун цэврийн байгууламжийн хангамж зэрэг үзүүлэлтүүд сөрөг хамааралтай гэсэн үр дүн гарсан. Түлхүүр үгс: Таталцлын загвар, Панел өгөгдөл, Гадаадын жуулчдын эрэлт, аялал жуулчлалын салбар